REDUCTION OF THE LOAD ON THE MAIN DRIVE SHAFT OF BAND SAWS - Sokolovski, Slavcho; Deliiski, Nencho (Innovation in Woodworking Industry and Engineering design, 2013)
Analysis of the load on the main drive shaft of band saw is provided in three cases:Bending couples resulting from the strain forces of the saw band and the belt transmission are absorbed by the shaft.• The bending couple resulting from the force of strain of the saw bend is absorbed by the shell of the bearing unit and the bending couple caused by the strain force of the belt transmission is received by the shaft.• Bending couples from the strain forces of the saw band and the belt transmission are received by the shell of the bearing unit.Strain forces of the saw band and the belt transmission loading the main drive shaft are determined. Validating test strength calculations of the main band saw shaft are made. Constructive solutions to reduce the bending in the console parts of the main drive shaft which will improve the work of the saw band and the V-belt transmission are proposed.